Mass Spectrometry Untangles Plant Membrane Protein Signaling Networks - Chen, Yanmei; Weckwerth, Wolfram (Trends in plant science, 2020)
Plasma membranes (PMs) act as primary cellular checkpoints for sensing signals and controlling solute transport. Membrane proteins communicate with intracellular processes through protein interaction networks. Deciphering these signaling networks provides crucial information for elucidating in vivo cellular regulation. Large-scale proteomics enables system-wide characterization of the membrane proteome, identification of ligand–receptor pairs, and elucidation of signals originating at membranes. In this review we assess recent progress in the development of mass spectrometry (MS)-based proteomic pipelines for determining membrane signaling pathways. We focus in particular on current techniques for the analysis of membrane protein phosphorylation and interaction, and how these proteins may be connected to downstream changes in gene expression, metabolism, and physiology. Membrane receptors, kinases, and transporters communicate with intracellular processes through protein interaction networks. Characterization of plant PM proteins – especially hydrophobic proteins – remains challenging despite advances in separation and analysis techniques.Rapid advances in MS instrumentation and data analysis have enabled marked progress in deciphering the membrane proteome and mapping protein interaction partners, leading to a better understanding of PM protein complexes.Analysis of membrane protein phosphorylation under specific cellular conditions is crucial for elucidating the molecular mechanisms underlying signal sensing, transport, and metabolic processes. Phosphoproteomics allows unbiased localization and site-specific quantification of in vivo protein phosphorylation, thus facilitating the dissection of membrane signaling networks.